Advancing gender equality in home-grown school feeding programs: An introductory framework - Zaremba, Haley; Elias, Marlene; Estrada Carmona, Natalia; Borelli, Teresa; Hunter, Danny; Shijagurumayum, Meghajit (2025)
In this brief, we propose a framework to conceptualize gender considerations in home-grown school feeding programs to inform research, practice, and policy. The framework maps interlinked and localized processes from production through to consumption, and the policy and institutional environments within which school feeding takes place, to identify entry points for gender-responsive programs. We argue that addressing gender issues and inequalities can lead to more holistic programs that advance equality and inclusion alongside other human development and environmental goals.